Magnetically controlled Growing Rods for Early-onset Scoliosis: A Multicenter Study of 23 Cases With Minimum 2 years Follow-up. Issue 18 (15th September 2016) - Hosseini, Pooria; Pawelek, Jeff; Mundis, Gregory M.; Yaszay, Burt; Ferguson, John; Helenius, Ilkka; Cheung, Kenneth M.; Demirkiran, Gokhan; Alanay, Ahmet; Senkoylu, Alpaslan; Elsebaie, Hazem; Akbarnia, Behrooz A.
Abstract : Study Design: Retrospective study. Objective: To report 2-year clinical and radiographic results of patients treated with magnetically controlled growing rods (MCGR). Summary of Background Data: MCGR for early-onset scoliosis has been reported to provide adequate spinal growth and curve correction by eliminating surgical lengthening procedures. This study was designed to report the results of MCGR patients with 2-year follow-up. Methods: A retrospective study of MCGR patients with the following inclusion criteria: (i) major curve size ≥30°, (ii) T1-T12 height <22 cm, (iii) <11-years old; all at the time of index surgery was performed. Of 54 patients enrolled, 23 had 2-year follow-up. Both primary and conversion patients were evaluated at baseline 6, 12, and 24 months. Results: Mean preoperative age in the primary group was 6.6 ± 2.6 years versus 8.3 ± 2.2 years for the conversion group. A total of 41 adverse events occurred in 11 patients, of which 14 events were implant related. Major coronal curve magnitude improved from 61.3° to 34.3° from baseline to postoperation in primary cases and from 49.4° to 43.8° in conversion cases. Curve correction was maintained for 2 years in both groups. T1-S1 height improved from 252.7 to 288.9 mm in primary cases and was maintained for 2 years. However, conversion cases had some decline in T1- S1 height (270.3 at baseline to 294.4 mm post-MCGR and 290.2 mm at 2-year follow-up; mean loss of 4.2 mm (1.5%) from postoperation to 2 years, P  > 0.05). Conclusion: This study showed satisfactory curve correction and growth is achieved among primary cases. T1-S1 height in conversion cases had a slight decline in 2 years. However, this decline was not statistically significant. Level of Evidence: 3